Analysis of Subject Concept Understanding Social Sciences in Grade IV Elementary School Students - Yohana Indriyanti; Bukman Lian; Adrianus Dedy (Indonesian Journal of Primary Education, 2022)
The purpose of this study was to determine the extent of understanding the concept of social studies subjects in fourth grade students. The research method used in this study is a qualitative descriptive method. Data collection techniques used in this study were interviews and documentation. The data obtained were then analyzed using a qualitative descriptive method. The results of this study indicate that the level of understanding of the concept of social studies subjects in fourth grade students of SD Negeri 138 Palembang is in the good category. This is proven based on the results of an evaluation conducted by researchers regarding the understanding of the concept of social studies subject matter of economic activities, there are 17 students who get scores above the KKM with a percentage of 65.38%,